A commentary on I Peter - Goppelt, Leonhard, 1911-1973; Hahn, Ferdinand, 1926-; Alsup, John E. 1941- (Grand Rapids, MI Eerdmans, 1993)
Includes bibliographical references and index.
Keywords: Bible. N.T. Peter, 1st -- commentaries